The effect of organizational justice on knowledge sharing: Empirical evidence from the Chinese telecommunications sector - Tayyaba Akram; Shen Lei; Muhammad Jamal Haider; Syed Talib Hussain; Lilian Consuelo Mustelier Puig (Journal of Innovation & Knowledge (JIK), 2017)
This study assessed the impact of organizational justice on knowledge sharing among employees of Chinese telecommunications firms. The study focused on five forms of organizational justice (distributive, procedural, interactional, temporal, and spatial) and two forms of knowledge sharing (donating and collecting). A self-administered questionnaire yielded data for 245 employees. The data were analyzed using a two-step process in Amos 21. First, the measurement model was determined through CFA. Second, SEM was applied to test the hypotheses. The results suggest that if employees have positive perceptions of distributive, procedural, interactional, and temporal justice, they are intrinsically encouraged to share their knowledge with colleagues. Spatial justice, however, was found to affect knowledge sharing negatively and significantly. In an organizational work context, each form of organizational justice has a unique contribution toward knowledge sharing. Therefore, all forms of organizational justice should be considered.
Keywords: A23; M10; 650; Organizational justice; Distributive justice; Procedural justice; Interactional justice; Temporal justice; Spatial justice; Knowledge sharing; China